Integrated exposure and risk characterization of bisphenol-A in Europe. (December 2016) - Sarigiannis, Dimosthenis A.; Karakitsios, Spyros P.; Handakas, Evangelos; Simou, Konstantina; Solomou, Ermioni; Gotti, Alberto
Abstract: The current study aims at a comprehensive risk characterization of bisphenol A (BPA) supported by an integrated exposure modelling framework that comprises far field and near field exposure modelling coupled to a dynamic lifetime PBTK model. Exposure analysis was done on European data of BPA food residues and human biomonitoring (HBM). The latter were further assimilated through an advanced exposure reconstruction modelling framework to estimate the corresponding external and internal systemic dose of BPA and its metabolites. Special attention was paid on the assessment of exposure to BPA during critical developmental stages such as gestation by modelling the mother-fetus toxicokinetic interaction. Our findings showed that current exposure levels in Europe are below the temporary Tolerable Daily Intake (t-TDI) of 4 μg/kg_bw/d proposed by the European Food Safety Authority. Taking into account age-dependent bioavailability differences, internal exposure of premature neonates hosted in intensive care units was reckoned close to the biologically effective dose (BED) resulting from translating the EFSA temporary total daily intake (t-TDI) into equivalent internal dose. Use of the ToxCast21 Biological Pathway Altering Dose (BPAD) as an alternative internal exposure reference value, resulted in increased margins of safety compared to the conventional exposure/risk characterization scheme. Highlights: Integrated exposure and risk analysis of bisphenol-A in Europe. Toxicokinetic modelling allowed us to account for age-dependent differences. Internal exposure to developing fetus during pregnancy is low. Infants hosted in neonatal intensive care units are the most vulnerable group. Internal dosimetry estimation caters for more robust risk characterization of BPA.